Thermal Structure of Subducting Slab along the Java Arc and Its Significance to the Volcanoes Distribution - Lina Handayani (Journal of Mathematical and Fundamental Sciences, 2010)
Java Island has a unique tectonic features and one of it is the pattern of the volcano distribution along the island. The volcano pattern occurrence might be connected to the deeper process of geodynamic. Hence, thermal structure modeling is employed to find any association between the subducting plate and the tectonic of the overriding plate. Thermal structure of a subducting plate depends on the age of the lithosphere and the dip of the subduction. With the lithospheric age increases from west to east of Java, varies from about 90 my to 120 my old, there are dissimilarities in thermal structure models. The comparison with volcanoes positions shows that differences of thermal structure might have associated to variation in the formation of volcanoes in Java Island.